COMPATIBILITY BETWEEN THE GREEN TARGET COST AND THE DISJOINTED ANALYSIS AND THEIR ROLE IN IMPROVING PRODUCT QUALITY AND REDUCING COSTS: AN APPLIED STUDY IN ALDIWANIYAH TIRE FACTORY - Zainab Hadi Mahdi; Shaima Yas Khudair (Scholar Express Journals, 2023)
The research aims to demonstrate the importance of compatibility between the green target costing technique and disassembled analysis in order to improve product quality and reduce cost, and to define the importance of disassembled analysis as an effective tool for determining the specifications and design of competing products and how the company develops its products to enter the competitive market with high quality. Green and its role in improving quality and reducing costs and the concept of disjointed analysis, and the importance of compatibility between the green target cost and disjointed analysis and their role in improving quality and reducing costs, The research presented a set of conclusions, including that green target costs are a modern technology for cost management and that its application contributes to linking the basic success factors of the company with the aim of increasing profitability and its ability to compete and survive by maintaining the quality of its products, by following advanced informational methods and techniques such as value analysis, Continuous improvement and disjointed analysis (value engineering), and that there is a similarity in the basic principles of disjointed analysis in most industries, as data is collected for analysis and evaluation, and disjointed analysis is also one of the most important methods that help the company to identify opportunities for product development and reduce costs by evaluating and analyzing competitors' products and knowledge of their specifications in order to reach conclusions about the process that was carried out by means of the manufacture and presentation of those products. The research recommends the need for integration between cost accounting techniques, including green target costing and disjointed analysis, in order to improve both product quality and reduce costs, as a result of the information provided by this compatibility that helps companies manage to achieve their goals
Keywords: green target cost; disjointed analysis; product quality; reducing costs